Occult major venous injury in penetrating thigh trauma: An underdiagnosed cause of morbidity and mortality - Naveen Balan; Dennis Y. Kim; Jessica Keeley; Angela Neville (Trauma Case Reports, 2023)
Background: There are no current consensus guidelines that address screening patients who may have occult major venous injury in the setting of penetrating thigh trauma. Yet, such injuries confer significant morbidity and mortality to trauma patients if left untreated. Methods: This paper examines the cases of three patients who presented to our single level I trauma center after sustaining penetrating thigh trauma with negative CT arteriography, all of whom were eventually diagnosed with occult major venous injury. Results: One patient developed massive pulmonary embolism with death and the other two patients required operative exploration due to a foreign body within a major vein and major venous hemorrhage. Conclusion: These cases underscore the importance of having a high index of suspicion for occult major venous injury in select patients with penetrating thigh trauma and negative CT arteriography. Level of evidence: V Study type: therapeutic/care management.